The 'Orthodoxy' of Orthodoxy: On Moral Imperfection, Correctness, and Deferral in Religious Worlds - Bandak, Andreas (Religion and society, 2014)
This article uses ethnographic studies of Orthodox Christianities as a way to investigate the concept of 'orthodoxy' as it applies to religious worlds. Orthodoxy, we argue, is to be found neither in opposition to popular religion nor solely in institutional churches, but in a set of encompassing relations among clergy and lay people that amounts to a religious world and a shared tradition. These relations are characterized by correctness and deferral—formal modes of relating to authority that are open-ended and non-definitive and so create room for certain kinds of pluralism, heterodoxy, and dissent within an overarching structure of faith and obedience. Attention to the aesthetics of orthodox practice shows how these relations are conditioned in multi-sensory, often non-linguistic ways. Consideration of the national and territorial aspects of Orthodoxy shows how these religious worlds of faith and deferral are also political worlds.